2022
DOI: 10.1021/acs.joc.2c02096
|View full text |Cite
|
Sign up to set email alerts
|

Concise Synthesis of Glycerophospholipids

Abstract: Glycerophospholipids are major components of cellular membranes and provide important signaling molecules. Besides shaping membrane properties, some bind to specific receptors to activate biological pathways. Untangling the roles of individual glycerophospholipids requires clearly defined molecular species, a challenge that can be best addressed through chemical synthesis. However, glycerophospholipid syntheses are often lengthy due to the contrasting polarities found within these lipids. We now report a gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In animals, phospholipids are hydrolyzed into glycerol, phosphate, choline, and ethanolamine by a series of phospholipases. Glycerophospholipids are major lipids in cell membranes and play important roles in cell signaling, G protein-coupled receptors, and ion transport ( 71 ). In the present study, serum levels of glycerophosphocholine, 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine, and 1-palmitoyl-sn-glycero-3-phosphocholine were decreased in Dazu black goats in response to HS ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, phospholipids are hydrolyzed into glycerol, phosphate, choline, and ethanolamine by a series of phospholipases. Glycerophospholipids are major lipids in cell membranes and play important roles in cell signaling, G protein-coupled receptors, and ion transport ( 71 ). In the present study, serum levels of glycerophosphocholine, 1,2-dioleoyl-sn-glycero-3-phosphatidylcholine, and 1-palmitoyl-sn-glycero-3-phosphocholine were decreased in Dazu black goats in response to HS ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two pathways were driven by deoxyguanosine and ethanolamine, respectively. The relative concentration of ethanolamine was lower in STC, compared to SUF sheep, and its associated glycerophospholipid metabolism was found to be a strong indicator of copper toxicity in pig kidney (Qiao et al, 2021;Bi et al, 2022;Mukhopadhyay and Trauner, 2023). Reduced relative concentration of ethanolamine in STC may suggest non-toxic liver tissue.…”
Section: Pathway Name Fdr Associated Metabolitesmentioning
confidence: 93%
“…Bio-membranes contain a significant amount of glycerophospholipids, which are known to control several cellular signaling events involving ion channels or G-protein coupled receptors. Protein translocation, apoptosis, inflammation, and neurogenesis are crucial in calcium homeostasis [80]. These studies suggested that active metabolic pathways and high abundance of metabolite contents may be important mechanisms for the resistance to PBD by the HR cultivars.…”
Section: Metabolomic Profiling Of the Stems Of Hr And Hs Sugarcane Cu...mentioning
confidence: 95%